2021
DOI: 10.1556/2006.2021.00058
|View full text |Cite
|
Sign up to set email alerts
|

The stock market as a casino: Associations between stock market trading frequency and problem gambling

Abstract: Background and aims Personal investors decrease their stock market investment returns by trading frequently, which the behavioral finance literature has primarily explained via investors' overconfidence and low levels of financial literacy. This study investigates whether problem gambling can help account for frequent trading in a sample of active gambler/investors, as suggestive of frequent trading being in part driven by a behavioral addiction to gambling-like activities. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Moreover, traders may develop cognitive biases, such as overconfidence or the illusion of control, leading them to believe they can consistently predict market movements and make profitable trades. These biases can perpetuate engagement in trading, even in the face of losses [ 1 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, traders may develop cognitive biases, such as overconfidence or the illusion of control, leading them to believe they can consistently predict market movements and make profitable trades. These biases can perpetuate engagement in trading, even in the face of losses [ 1 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows a summary of the most important differences and similarities between both industries and lists the main implications. Research suggests that some parts of the financial markets possess addictive properties (Granero et al, 2012 ; Fong, 2014 ; Arthur et al, 2016 ; Cox J. et al, 2020 ; Cox R. et al, 2020 ) and individuals who are active in the financial markets are showing signs of gambling-related problems (Guglielmo et al, 2016 ; Grall-Bronnec et al, 2017 ; Cox R. et al, 2020 ; Mosenhauer et al, 2021 ). Studies also show that certain gamblers substitute their desire to gamble with a wide range of financial products indicating a direct link between both markets (Dorn et al, 2015 ; Cookson, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Speculative investments are high-risk and short-term (e.g., day-trading and penny stocks) and may also involve the use of certain speculative strategies such as leverage, shorting and derivatives (Oksanen et al 2022a;Arthur et al 2016). Two recent studies have found that investors with greater compulsive gambling symptoms were twice as likely to invest in derivatives and leveraged products than baseline investors (Cox et al 2020) and that problem gambling was significantly associated with frequency of trading (Mosenhauer et al 2021). Gambling and trading therefore intersect in several ways.…”
Section: The Gamblification Of Investingmentioning
confidence: 99%